TRANSFORMATION OF THE ANCIENT WORLD IN THE PLOT OF THE NOVEL "MEDEA" K. WOLF (European Journal of Interdisciplinary Research and Development, 2023)
The relevance of the chosen topic lies in setting of a broad cultural problem – the problem of intermediality, which is being developed by Russian and foreign researchers. The aim of the work is to identify the manifestations of the principles of intermediality in different kinds of art of the second half of the XX century based on a comprehensive analysis.